THE USE OF DIGITAL TECHNOLOGIES IN THE EDUCATION OF THE 21ST CENTURY - Santana Bittencourt, Priscilla Aparecida [UNESP]; Albino, Joao Pedro [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2017)
This research has provided a brief overview of the topics related to digital natives and education in the 21st century. The use of technologies in education has been a challenge with some open questions, such as: why and how to use digital media in education and what media to use. The ease of access of digital technologies by young people requires the teaching -learning process to adapt, to prepare and develop critical and active citizens. In order to collect data and reflect on digital technologies and their use in the educational process of digital natives, a bibliographical research was first carried out on the origin of digital natives and their correlation with information and communication technologies. Subsequently, quantitative and qualitative research will be developed to be applied in the academic community (students and teachers) in two middle schools, one public and one private. The results will be analyzed and compared with the objective of validating the research question and contribute to discuss the challenges and possibilities of the use of technologies in education. To date, it may be inferred that further study is needed on the concept of digital media and its use in the educational process.
Keywords: Digital natives; Technologies; Education; Teaching-learning